Addressing the Tragedy of Common's through Community Innovation in Nepal - Paudel, Shambhu; Bhatt, Bharat (The Initiation, 2011)
Hardin’s “The Tragedy of the Commons” speaks about the problems in common resources and this applies highly in the community forestry in Nepal. Annapurna Conservation Area and Community forestry have already shown the proven record of success in community participation. However, the willingness of getting high share in the common property and taking least care has been the major problem. This can be properly addressed through the proper community participation. This article speaks about the ways of addressing the tragedy of commons through community innovation and already being practiced model. DOI: http://dx.doi.org/10.3126/init.v4i0.5540 The Initiation Vol.4 2011 92-95